Federalism: Challenges and Opportunities in Nepal - Gyawali, Gokarna P. (Molung Educational Frontier, 2018)
It is assumed that the main aspect of the Constitution of Nepal promulgated on September 20, 2015 is the transfer of power from central/federal to the provincial and local government. However, the devolution process has not been satisfactorily experienced as had been expected when it was promulgated by the overwhelming majority of the then Constituent Assembly. One of the reasons for this slow progress might be some confusion and/ or problem in matters of power sharing between different levels of governments. So, the primary objective of the researcher is to review the power sharing modality existing in the new constitution on different sectors and areas of the state machinery. This paper focuses on the federal structure, demography, power sharing between the provincial and local level, opportunities and challenges of federalism in Nepal. It argues that the restructuring initiatives have not been successful in minimizing the political, social, economic, regional and ethnic inequalities that were inherent in the previous political systems for nearly 240 years of a unitary system of governance in Nepal. This paper also explores the implications of Nepal‘s new Federal Constitution for local governance, fiscal policies, cultural identity and other related issues.